Lung cancer risk and occupational exposures in crop farming: results from the AGRIculture and CANcer (AGRICAN) cohort. Issue 11 (5th September 2018) - Boulanger, Mathilde; Tual, Séverine; Lemarchand, Clémentine; Guizard, Anne-Valérie; Delafosse, Patricia; Marcotullio, Elisabeth; Pons, Romain; Piel, Clément; Pouchieu, Camille; Baldi, Isabelle; Clin, Bénédicte; Lebailly, Pierre
Abstract : Objectives: Farmers are considered at lower risk of lung cancer. However, specific tasks can expose them to hazardous air contaminants such as pesticides, diesel exhaust and mineral dust. This study aimed to assess the associations between various crops and related tasks and the risk of lung cancer, overall and by histological subtypes. Methods: AGRIculture and CANcer is a prospective French cohort of individuals affiliated to the agricultural health insurance scheme. Incident lung cancers (n=897) were identified by cancer registries from enrolment (2005–2007) to 2013. Data on crop and livestock exposure during lifetime were obtained from the enrolment questionnaire. We used a Cox model with attained age as timescale, adjusted for gender, smoking history and exposure to cattle and horses. Effects of duration and surface were assessed and analyses stratified on gender and smoking status were performed. Results: Winegrowers were at higher risk of adenocarcinoma (HR=1.27 (95% CI 0.94 to 1.72)). We also found an association between pea growing and small cell lung cancer: significant effect of duration (ptrend =0.04) and the suggestion of a surface–effect relationship (ptrend =0.06); increased risk (HR=2.38 (95% CI 1.07 to 5.28)) for pesticide users; and significant effect of duration (ptrend =0.01) for harvesters. The risk of squamous cell carcinoma was increased for sunflower growing (HR=1.59 (95% CI 0.97 to 2.62), fruit-tree pruning (HR=1.44 (95% CI 0.92 to 2.27)) and pesticide use on beets (HR=1.47 (95% CI 0.92 to 2.34)). Corn and/or wheat/barley growers were at lower risk of lung cancer. Conclusions: Our results suggest associations between lung cancer and several crop-related tasks, even if we cannot rule out some chance findings due to multiple comparisons.